Liver enzymes among COVID-19 patients in Al-Ahsa region of Saudi Arabia - Omar AlOmair (BMJ Open Gastroenterology, 2023)
Background Hepatic damage is one of the common forms of extra pulmonary organ destructions among patients with COVID-19 infections.Aim To evaluate the prognosis of liver damage among COVID-19 patients based on their liver enzymes profile.Methods A retrospective study was done to evaluate the records of the hospitably admitted patient due to COVID-19 infection.Retrieved data included clinical presentation and investigation either imaging or laboratory with special investing in liver function tests.Result We reviewed 442 patients who were diagnosed with COVID-19 infection.They were 64.5% of female patients and 35.5% of male patients. Their mean age was 54.5%, most of them were Saudi (76.7%) and the overall mortality reached up to (20.4%).Conclusion This large cohort of 442 patients has shown that liver damage may be an independent prognostic factor for morbidities and mortality among COVID-19 patients. It also showed the importance of liver function enzymes screening as a predictor for the outcome of those patients.